Southern Armyworm, Spodoptera eridania (Cramer) (Insecta: Lepidoptera: Noctuidae) - John L. Capinera (EDIS)
This document is EENY-106, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 1999. Reviewed May 2003.